2015
DOI: 10.1080/20786190.2014.978106
|View full text |Cite|
|
Sign up to set email alerts
|

Cannabis and mental illness in adolescents: a review

Abstract: REVIEWSouth African Family Practice 2016 ; 58(S1):S18-S21 http://dx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…Beyond these, the current evidence of marijuana use being associated with increased odds of suicidal behavior is consistent with key findings by earlier and recent primary studies and systematic reviews (Almansour & Siziya, 2017;Borges & Loera, 2010;Carvalho et al, 2019;Gobbi et al, 2019;Tetteh et al, 2020). Evidence suggests that marijuana use has adverse health outcomes among adolescents: it impairs memory and judgement, and complicates the course of loneliness and depression, thereby elevating the risk for suicidal behaviors (Borges & Loera, 2010;Paruk & Burns, 2016;Volkow et al, 2014). Urgent concerted efforts are needed to formulate and implement regulations and control measures and policies against the unfettered access and use of marijuana (and other illicit drugs) by young people in the Eswatini (Mkhatshwa & Malambe, 2019).…”
Section: Factors Associated With Suicidal Behaviorssupporting
confidence: 83%
“…Beyond these, the current evidence of marijuana use being associated with increased odds of suicidal behavior is consistent with key findings by earlier and recent primary studies and systematic reviews (Almansour & Siziya, 2017;Borges & Loera, 2010;Carvalho et al, 2019;Gobbi et al, 2019;Tetteh et al, 2020). Evidence suggests that marijuana use has adverse health outcomes among adolescents: it impairs memory and judgement, and complicates the course of loneliness and depression, thereby elevating the risk for suicidal behaviors (Borges & Loera, 2010;Paruk & Burns, 2016;Volkow et al, 2014). Urgent concerted efforts are needed to formulate and implement regulations and control measures and policies against the unfettered access and use of marijuana (and other illicit drugs) by young people in the Eswatini (Mkhatshwa & Malambe, 2019).…”
Section: Factors Associated With Suicidal Behaviorssupporting
confidence: 83%
“…Regular use of marijuana during adolescence is of particular concern due to the associated likelihood of adverse health consequences, including the impairment of memory, judgement and personality; 10 it has also been implicated for increased risk of moderate to severe negative mental health outcomes including bipolar, mood disorders, anxiety, cognitive, depressive disorders, suicide attempt and eventual suicide. 11 …”
Section: Introductionmentioning
confidence: 99%
“…The review of 68 articles by Memedovich, Dowsett, Spackman, Noseworthy and Clement (2018) revealed that marijuana is a risk factor health disorder, brain change, and cognitive outcome. A review by Paruk and Burns (2015) tried to ascertain the relationship between marijuana exposure and mental illness in adolescents drawing from a review of studies, the study concludes that marijuana use can be considered a risk factor for mental illnesses in later life. Hanna, Perez and Ghose (2017) review on cannabis and its association with psychiatric disorder found as a substantial relationship between cannabis and increase risk of psychosis disorder.…”
Section: Empirical Evidence Of Marijuana and Mental Healthmentioning
confidence: 99%